Teacher Job Performance: The Role of Head Teachers’ Supervisory Styles in Public Basic Schools in Mankessim Circuit - Appiah, Alex Kojo; Esia-Donkoh, Kweku (International Journal of Educational Studies, 2018)
The study investigated the effect of head teachers’ supervisory styles and teachers’ job performance in public basic schools in the Mankessim Education Circuit of the Mfantseman Municipality in the Central Region of Ghana. A descriptive survey in the form of mixed methods was used for the study. Through purposive and stratified sampling techniques, 134 respondents made up of 16 head teachers, and 118 teachers were selected and engaged in the study. Two sets of questionnaires, one each for head teachers and teachers were used to collect quantitative data. Qualitative data were obtained through a semi-structured interview guide from 10 respondents (headteacher and teachers) who were conveniently sampled. Means, standard deviation, t-test, one-way ANOVA, and multiple regression were used to analyze the quantitative data while content analysis was used to analyze the qualitative data. The study revealed that head teachers used directive control supervisory style most frequently as compared to collaborative, directive informational, and non-directive supervisory styles. Generally, teachers’ job performance was very good. Besides, the study discovered that head teachers’ supervisory styles were good predictors of teachers’ job performance. It was concluded that supervisory styles of head teachers were essential factors that influenced teachers’ job performance in schools. Among the recommendations is that in-service training in the form of workshops and seminars should be organized for both head teachers and teachers on the need for effective supervision in public basic schools in the Circuit to achieve school and educational goals.